Lovell's gazetteer of British North America [electronic resource] : containing the latest and most authentic descriptions of over six thousand cities, towns and villages in the provinces of Ontario, Quebec, Nova Scotia, New Brunswick, Newfoundland, Prince Edward Island, Manitoba, British Columbia, and the North West Territories - Crossby, P. A. (Peter Alfred), b. 1842. (Montreal; Rouse's Point, N.Y. : Lovell Print. and Pub. Co., 1877)
The 2nd v. has special t.p.: The railway and steamboat routes in British North America . by P.A. Crossby. Tables. Other title information: And general information, drawn from official sources, as to the names, locality, extent, etc., of over fifteen hundred lakes and rivers, with a table of routes, showing the proximity of the railroad stations, and sea, lake and river forts, to the cities, towns, villages, etc., in the several provinces. 2 v. in 1. Electronic reproduction. Mode of access: Internet. 44